2001
DOI: 10.1116/1.1410089
|View full text |Cite
|
Sign up to set email alerts
|

Direct measurement of Coulomb effects in electron beam projection lithography

Abstract: Demagnifying immersion magnetic lenses used for projection electron beam lithography without crossoversScaled measurements of global space-charge induced image blur in electron beam projection system

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…7 This method consisted of slit patterns on a Si membrane ͑2 m thick͒, two limiting apertures, and a sensor of a photodiode detector. 1͒.…”
Section: A Beam Blur Measurement Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 This method consisted of slit patterns on a Si membrane ͑2 m thick͒, two limiting apertures, and a sensor of a photodiode detector. 1͒.…”
Section: A Beam Blur Measurement Methodsmentioning
confidence: 99%
“…Some of the space charge effect, an averaged electric field emulated analytically, can be corrected by refocusing. 7 We found that beam blur dependence on beam current was 5.4 nm/ A. In our previous paper 6 we analyzed the influence of the Coulomb effects on the EPL process based on our experimental results.…”
Section: Introductionmentioning
confidence: 94%
“…The beam current affects the results of the correction because the forward-scattering range, including the beam blur, increases as the beam current increases. 14) We divided the measured patterns and dummy patterns into different masks, which resulted in a small opening ratio for the mask containing the measured patterns. Large patterns, as shown in Fig.…”
Section: Complementary Mask Splitmentioning
confidence: 99%
“…5,6 When higher beam current is used to improve throughput, the Coulomb effects, consisting of global space charge and stochastic Coulomb effects, 7,8 cause defocus and beam blur, compromising resolution. 1 and 2) is an attractive candidate for nextgeneration lithography because of its high-resolution capability of 65 nm or less, especially for contact hole and gate layers.…”
Section: Introductionmentioning
confidence: 99%